THE UTILIZATION OF GLYCEROL, BIODIESEL SIDE PRODUCT OF USED COOKING OIL AS GLYCEROL ACETATE MATERIAL SYNTHESIS - Heri Wibowo (Jurnal Penelitian Saintek, 2015)
The research aimed at using glycerol of biodiesel synthesis side product from used cooking oil as glycerol acetate material synthesis, and charactering synthesized material based on data of IR spectroscopy and GCMS. The method used to synthesize glycerol acetate was reﬂ ux during 50 minute at 80 C. Glycerol from biodiesel synthesis side product from used cooking oil was puriﬁ ed with acetic anhydride reacted at 80 0 C, for 50 minutes. The synthesis product was characterized by IR and GCMS spectroscopies. The result of this research shows that glycerol derived from synthesizing glycerol 1–monoacetate and glycerol 2-monoacetate in the form of yellow liquid with 145 148 0 0 C boiling point, soluble in ethanol and insoluble in n-hexane. IR spectrum shows the presence of C=O carbonyl, C-O ester, -OH, and C-H aliphatic group; GCMS spectrum shows a mixture from two glycerol monoacetate with SI (Similiar Index) of 97 and 93.